Knowledge, Attitude, and Practices on HIV Preventive Measures Among Students of Lira University, Lira City: A cross-sectional study. - Otike, Francise; Namukasa, Ms. Shamim; Ayikobua, Dr. Keren Carol Drateru (Student’s Journal of Health Research Africa, 2026)
Background: Despite decades of global health campaigns, HIV/AIDS remains a major public health issue, particularly among adolescents and young adults. This study aimed to assess the knowledge, attitudes, and practices (KAP) regarding HIV transmission and prevention among Lira University students. Methodology: A descriptive cross-sectional study was conducted among 183 university students using a structured self-administered questionnaire. Data were analyzed using SPSS version 20, and results were presented in tables and figures. Results: The majority of participants were aged 18–21 years (55%), 53% were male. In terms of knowledge, 70% had received formal education on HIV/AIDS, with 49% recognizing unprotected sex as a transmission mode, and only 30% were aware of PrEP. For attitudes, while 89% acknowledged HIV/AIDS as a serious issue, 69% expressed negative attitudes toward regular HIV testing, and 57% were unwilling to interact with HIV-positive individuals. Regarding practices, 62% had never been tested for HIV, only 20% reported consistent condom use, and 67% had never used or encouraged others to use PrEP. Conclusion: Despite moderate knowledge, significant gaps in attitudes and preventive practices were noted, and misconceptions and stigma remain barriers to effective HIV prevention. Recommendations: Comprehensive sexual health education should be integrated into all university programs. Stigma-reduction campaigns and accessible, youth-friendly HIV services are also essential to promote behavior change and reduce new infections among students.